Relations hommes - canidés de la préhistoire aux périodes modernes - Boudadi-Maligne, Myriam; Mallye, Jean-Baptiste (DAN@, 2020)
The study of Human-Carnivore interactions constitutes an important line of research for the study of human societies and their relationship with the natural world. Among Carnivores, Canids are omnipresent in archaeological sites. With respect to their roles as competitors, commensals, a food source, pets, burial partners, canids offer a vast field of research in archaeology. Recent research in taphonomy, zooarchaeology, morphometrics and paleogenetics has offered new perspectives on the relationships that may have existed between these carnivores and past human societies. This volume brings together some of this recent work and illustrates the diversity of approaches used to study Human-Canid relationships over time.